GEOWISATA GEOPARK CILETUH: GEOTREK MENGELILINGI KEINDAHAN MEGA AMFITEATER CILETUH (THE MAGICAL OF CILETUH AMPHITHEATER) - Andriany, Suci Sarah; Fatimah, Mega Rosana; Hardiyono, Adi (Fakultas Teknik Geologi Universitas Padjadjaran, 2016)
Ciletuh National Geopark region which administratively located in the District of Ciemas and Ciracap, Sukabumi, West Java province has a unique geodiversity and showed the oldest rocks in West Java. Because the geological characteristic that is not found in other places makes Ciletuh as National Geopark in Indonesia. In carrying out the Geopark concept, supporting activities that related with sustainable economic on that area, called Geotourism. The objective of this paper is to determine the Geotourism potential activities to do in the Ciletuh National Geopark, particularly reviewing Ciletuh Amphitheatre. The method used in this study is divided into three processes: starting from literature research areas and collection of field data as one step in the inventory of geological sites (geosites), followed by analysis and classification of data in accordance with the goal of this research. Geotrek with the theme of